"Evasão presencial" nas aulas de Educação Física: percorrendo caminhos através de narrativas - Souza, Olga da Silva (2024)
The present study aims to understand the motivation behind the increase in student absence from Physical Education (PE) classes as they progress through the basic education grades. The refusal to participate in the activities proposed and carried out in these classes generated the characteristic in this study called "face-to-face evasion". Faced with this problem, the objective of this study is to analyze the perception that students in the final years of Elementary School have about theicccccr participation in Physical Education classes, in an attempt to identify the trajectory that precedes the dropout process in these classes. The research was based on a qualitative approach, using a biographical narrative as a method. The target audience was made up of 16 students in the 9th grade of Elementary School, enrolled in a public school in the city of São Paulo/SP. The gathering of biographical data occurred through written narratives, of events already experienced by the interviewees. The analysis of the collected data and written productions was carried out in two stages: transcription and thematic analysis, arriving at the following categories: 1st) Thematization of school PE: between the ideal and the real: in which we can identify that students build their opinions about school PE as they’ve participated (or not) in classes, therefore, positive or negative experiences are decisive for participation or dropout in PE classes; 2nd) Bullying: (one of the forms of violence: which is recognized as a form of violence present in any school environment, including PE classes, wherever the body is often exposed in a humiliating and aggressive manner. The method in which this phenomenon is addressed and determines whether or not students choose to get involved in the proposed bodily practices; 3rd) Gender and sexuality oppression in PE classes: lack of understanding and value for differences and slight for diversity, make PE classes a emplacement of exclusion for those who do not fit into society's normative standards. Social interactions in classes are an opportunity for students and teachers to interact in order to inhibit any form of prejudice. The research achieved its main objective, which was to analyze the students' perception of their participation in PE classes. Through the collaboration of the interviewees, it was also possible to verify that in-person dropout rates in school PE classes are multifactorial, highlighting the importance of proposing inclusive and diverse practices, which consequently makes it easier in the complex social interaction between students.